2006
DOI: 10.1197/j.aem.2005.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Guideline Information without Patient Specificity in a Commercial Emergency Department Computerized Order‐entry System

Abstract: Adherence to an ACS guideline did not improve with implementation of a commercial ED information system without provision for patient-specific decision support. This suggests that the lack of patient-specific decision-support functionality in most current ED information system products may hamper progress in the development of effective decision support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Technology adaptation such as CPOE can be influenced by physician resistance (47), organisational factors (48), hospital characteristics regarding economic profile, poor integration into workflow (20,47), ownership and environmental factors such as competition and technology adaptation behaviour of neighbouring hospitals (49). In addition to these universal factors, the lack of healthcare workforce is the main problem in our health system.…”
Section: Discussionmentioning
confidence: 99%
“…Technology adaptation such as CPOE can be influenced by physician resistance (47), organisational factors (48), hospital characteristics regarding economic profile, poor integration into workflow (20,47), ownership and environmental factors such as competition and technology adaptation behaviour of neighbouring hospitals (49). In addition to these universal factors, the lack of healthcare workforce is the main problem in our health system.…”
Section: Discussionmentioning
confidence: 99%
“…15 The guidelines had a general two-page sheet that included four different risk categories of ACS, followed by three different two-to three-page orders for each of the different categories (high and intermediate risk were combined into one set). Default selection of a set was not supported, thus requiring each order to be individually selected.…”
Section: Discussionmentioning
confidence: 99%
“…16 Asaro et al found no improvement with compliance of ACS medications; the best compliance was noted in the original simple order sheet before any interventions. 15 They attributed the lack of improvement to limited functionality in the system and the fact that the CDSS relied on clinicians actively seeking it out through a number of information-only fields. These were rarely accessed, and the appropriate order sets for a particular at-risk group were only used 47% of the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMRs have also been shown to offer improved accessibility, legibility and flexibility as well as a potential for reduction in medication errors [4]. Additionally, clinical decision support (CDS) within EMRs can support adoption of clinical practice guidelines [5], particularly when guidance is customized to both the provider and the patient [6].…”
Section: Introductionmentioning
confidence: 99%